Utilization of Ziziphus Mauritiana Leaves for Lowering Cholesterol Level - Linda Rosalina; Devin Mahendika; Muhammad Mikail Athif Zhafir Asyura; Syahrul Abdul Aziz; Tanwir Djafar (Postgraduate, University of Mataram, 2023)
Abstract: Indonesia as a region with a tropical climate has a variety of plants spread across various regions. These plants contain many chemicals that can easily be used as traditional medicine, one of which is bidara leaves (Ziziphus Mauritiana). Bidara leaves are not only used by people in China, but Indonesian people also use Ziziphus Mauritiana as a medicine for dysentery, diarrhea and gum swelling. Wide distribution and in large quantities in Indonesia makes it easy for people to cultivate and use it. Much research has been conducted to discuss the efficacy of Ziziphus Mauritiana. The research aims to determine the various benefits of Ziziphus mauritiana leaves which have been scientifically proven through research in Indonesia. Method: Conduct a literature search using the Google Scholar application and analyze the literature that meets the inclusion criteria. Results: From the search results and research results, we concluded about the benefits of Ziziphus mauritiana leaves. Conclusion: The greatest benefit of Ziziphus mauritiana leaves is as an antimicrobial, apart from that there are many other benefits such as analgesic, antipyretic and anti-inflammatory, anticancer, and functions as a plant that can reduce cholesterol levels in the leaves.